Efeitos de diferentes condições de feedback sobre a aquisição e manutenção de respostas e generalização via instrução programada - Costa, Rachel Candido Cespedes da (2020)
Behavior analysis has assessed education and has developed teaching technologies, including programmed instruction. The effects of manipulations on feedback have been one of the variables that has been investigated. This study aimed to investigate the effects of knowledge of correct response feedback (KCR) combined with the review feedback of the incorrectly completed frames until the answer is correct (AUC) on the acquisition and maintenance of responses, besides the generalization of the stimulus control for a new academic repertoire. In this study, 18 undergraduate students were allocated to three experimental conditions: (1) KCR for all frames, which was combined with AUC; (2) KCR for error, which was combined with AUC; (3) only AUC. All participants took part of pre-test, teaching procedure and post-test stages, and were also invited to perform the generalization and maintenance data collection. The results indicate that all conditions promoted better averages of correctness in the tests and demonstrated that KCR is an important variable to promote generalization. Further studies are suggested to explore other effects of feedback